Review on the Role of Corporate Governance and Internal Control System on Firms’ Financial Performance - Hazzaa, Omar Turki; Abdullah, Dewi Fariha; Dhahebi, Adel Mohammed (Asian Journal of Accounting Perspectives, 2022)
Research aim: This research analyses the systematic review of the literature (2015–2021) concerning corporate governance, internal control system, and their impact on financial performance. This study brings about several findings on the role of corporate governance mechanisms such as internal controls, the board size, independence, audit performance on the financial performance of firms. The findings suggested that the internal controls and board characteristics are critical for achieving good corporate governance. Design/Methodology/Approach: Literature review of previous studies on corporate governance’s role in improving financial performance. Research findings: The key findings of this review paper showed the importance of internal controls and board characteristics for the success and sustainability of firms. Practitioner/Policy implications: The findings of this paper are beneficial for small and medium–sized firms to implement good corporate governance to ensure the success and sustainability of their product and services. Research limitations: This review is limited to the concept of corporate governance, internal control system, theories of corporate governance, financial performance, board characteristics, and recent articles on this topic. Keywords: Corporate governance, internal control system, financial performance, agency theory, resource dependence theory Type of article: Literature review JEL Classification: G32, G34, G41, O16